2022
DOI: 10.7717/peerj.13864
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for dental erosion: a systematic review of in vitro studies

Abstract: Background Dental erosion is a chemical loss of the mineralized dental tissue caused by exposure to nonbacterial acids. Different treatment protocols have been adopted with the use of fluoride compounds to promote the formation of a layer of mineral precipitation in eroded lesions. Aim This systematic review aimed to evaluate the main treatments for dental erosion. Methodology This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(57 reference statements)
2
2
0
Order By: Relevance
“…Indeed, CPP-ACP can provide effective remineralization against erosion caused by orange juice [ 51 ], increasing the hardness and density of the erosive surface of the tooth [ 52 ] and reducing the depth of lesions [ 53 ]. Furthermore, the CPP-ACP-containing mousse tested in our study may be more effective in erosion lesions due to its very low pH, in agreement with other reports [ 54 , 55 ]. Since F-ACP and NaF varnish are used for the prevention of enamel loss due to tooth erosion in primary teeth, parents can turn to CPP-ACP mousse or NaF-containing varnish for their children, instead of opting for less-effective fluoride-containing toothpastes.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, CPP-ACP can provide effective remineralization against erosion caused by orange juice [ 51 ], increasing the hardness and density of the erosive surface of the tooth [ 52 ] and reducing the depth of lesions [ 53 ]. Furthermore, the CPP-ACP-containing mousse tested in our study may be more effective in erosion lesions due to its very low pH, in agreement with other reports [ 54 , 55 ]. Since F-ACP and NaF varnish are used for the prevention of enamel loss due to tooth erosion in primary teeth, parents can turn to CPP-ACP mousse or NaF-containing varnish for their children, instead of opting for less-effective fluoride-containing toothpastes.…”
Section: Discussionsupporting
confidence: 93%
“…Devadiga et al [18] found that agents containing CPP-ACP and β-TCP increased hardness of erosive tooth surface. Findings of our study, which agreement with the literature [13][14][15], it is stated that GC-ToothMousse cream may be more effective against Sensodyne Promine and Agarta in erosion lesions due to its very low pH. It is thought that our study will be a reference on the micro-CT studies on the remineralization effect of CPP-ACP-containing creams on demineralization lesions caused by erosion.…”
Section: Discussionsupporting
confidence: 91%
“…Although there was no statistical difference, Agarta provided the least decrease in the lesion area, and the maximum decrease was in the Sensodyne promine against the initial caries group. In many studies, the effectiveness of fluoride and CPP-ACP have been proven [6,13]. Nowadays, many parents tend to prefer herbal agents because of their chemical content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation